Interleukins and Ischemic Stroke - Zhu, Hua; Hu, Siping; Li, Yuntao; Sun, Yao; Xiong, Xiaoxing; Hu, Xinyao; Chen, Junjing; Qiu, Sheng (Frontiers in Immunology, 2022)
Ischemic stroke after cerebral artery occlusion is one of the major causes of chronic disability worldwide. interleukins (ILs) play a bidirectional role in ischemic stroke through information transmission, activation and regulation of immune cells, mediating the activation, multiplication and differentiation of T and B cells and in the inflammatory reaction. Crosstalk between different ILs in different immune cells also impact the outcome of ischemic stroke. This overview is aimed to roughly discuss the multiple roles of ILs after ischemic stroke.